Operation survival - Dixon, Franklin W. (New York : Aladdin Paperbacks, 2005)
Frank and Joe try to determine the cause of recent injuries and deaths at a camp for troubled teens in the wilderness surrounding Moosehead Lake in Maine.
Keywords: Hardy Boys (Fictitious characters) -- Fiction; Problem youth -- Fiction; Detective and mystery stories; Moosehead Lake (Me.) -- Fiction